Representation Of Women's Beauty In Indonesia In Imperfect Film: Career, Love And Scales - Sazudda, Hanna Nur; Malik, Nugraha Abdul; Nurfalah, Farida; Wulandari, Sri (Riviera Publishing, 2024)
This study examines the representation of beauty and physical appearance associated with the double standards faced by Indonesia women, as depicted in the film